Symboliczna topografia życia Edypa. Kilka uwag - Wesołowska, Elżbieta (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2021)
The author of Oedipus Rex manages to reconstruct the hero’s life path against the background of the map of Greece of his day. In doing so he constructs the imaginary of the protagonist’s identity, one that is inextricably linked to his mental blindness as opposed to the tragic, self-inflicted blindness meted out to himself as a punishment for his crimes.